Parque Lineal Mirolindo Diseño Urbano Del Parque Lineal Como Elemento Articulador y De Espacio Pùblico Entre El Canal De Mirolindo y La Ciudad De Ibagué, Tolima (2020)
This proposal favors the access of citizens to green public spaces, as linear parks where they can interact with nature creating social, cultural, sports, economic integration strategies and a great balance ecological.